Acupuncture combined with traditional Chinese medicine preparation for the treatment of marrow suppression after chemotherapy: A protocol for systematic review and meta-analysis. Issue 43 (29th October 2021) - Zhu, Qiongjie; Xu, Wenjin; Li, Xuesong
Abstract: Background: From the perspective of evidence-based medicine, the efficacy and safety of combined therapy for marrow suppression after chemotherapy is still unclear. Given that there is no high-quality meta-analysis to incorporate existing evidence, the purpose of this protocol is to design a systematically review and meta-analysis of the level I evidence to ascertain the efficacy and safety of acupuncture combined with traditional Chinese medicine preparation for marrow suppression after chemotherapy. Methods: The following databases will be searched electronically by keyword combination mode: 4 British literature databases including PubMed, EMBASE, Scopus, and Cochrane Library, and 4 Chinese literature databases, including Chinese national knowledge infrastructure, VIP, and Wan fang database. The randomized controlled trials on acupuncture plus traditional Chinese medicine preparation for marrow suppression after chemotherapy will be included. The primary outcome is the elevation of hemoglobin, platelets, leukocytes, and neutrophils. The other outcomes include clinical symptoms, quality of life, and absolute value of reticulocyte. Risk bias analysis of the studies will be performed independently by 2 reviewers using the Cochrane Risk of Bias Assessment Tool. Results: The review will add to the existing literature by showing compelling evidence and improved guidance in clinic settings. Conclusion: This protocol will provide a reliable theoretical basis for the following research.